Women in the films of John Ford - Meuel, David, 1950- (McFarland & Company, Inc., Publishers, 2014)
"While John Ford (1894-1973) remains one of the most influential and revered directors in film history. Taking a fresh look at dozens of Ford films, both familiar favorites and under appreciated gems, it focuses on the complex and diverse female characters in them as well as the actresses who so ably told their stories"--